FXTAS in an unmethylated mosaic male with fragile X syndrome from Chile. (13th October 2013) - Santa María, L.; Pugin, A.; Alliende, M.A.; Aliaga, S.; Curotto, B.; Aravena, T.; Tang, H.‐T.; Mendoza‐Morales, G.; Hagerman, R.; Tassone, F.
<x xml:space="preserve">Abstract</x> Carriers of an FMR1 premutation allele (55–200 CGG repeats) often develop the neurodegenerative disorders, fragile X‐associated tremor/ataxia syndrome (FXTAS). Neurological signs of FXTAS, parkinsonism and rapid onset of cognitive decline have not been reported in individuals with an unmethylated full mutation (FM). Here, we report a Chilean family affected with FXS, inherited from a parent carrier of an FMR1 unmethylated full mosaic allele, who presented with a fast progressing FXTAS. This case suggests that the definition of FXTAS may need to be broadened to not only include those with a premutation but also those with an expanded allele in FM range with a lack of methylation leading to elevated FMR1‐mRNA expression levels and subsequent RNA toxicity.